2019
DOI: 10.1111/aec.12754
|View full text |Cite
|
Sign up to set email alerts
|

Riparian zone as a main determinant of the structure of lizard assemblages in upland Amazonian forests

Abstract: The use of lizards as model organisms in ecological studies is based on their success in occupying a great diversity of habitats, and some species are closely tied to the environment, which is disadvantaged by the legislation of several countries concerning land use. Our aim was to relate lizard species distribution patterns in rainforest environments to variation in environmental gradients, and provide ecologically based metrics for establishing buffer zones around streams. Lizards were sampled three times in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…This effect has been reported in previous studies on herpetofauna (e.g. Vonesh 2001;Whitfield et al 2007;Folt and Reider 2013;) and could be related to an increase of prey and refuge availability both for lizards and snakes (Vitt et al 2008;Fraga et al 2013a;Faria et al 2019). Stream size was not related to either abundance or richness of squamates, as observed for frogs in the same study area (Tsuji-Nishikido and Menin 2011), indicating that lizard and snake assemblages are not strongly related to structural characteristics of these water bodies.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This effect has been reported in previous studies on herpetofauna (e.g. Vonesh 2001;Whitfield et al 2007;Folt and Reider 2013;) and could be related to an increase of prey and refuge availability both for lizards and snakes (Vitt et al 2008;Fraga et al 2013a;Faria et al 2019). Stream size was not related to either abundance or richness of squamates, as observed for frogs in the same study area (Tsuji-Nishikido and Menin 2011), indicating that lizard and snake assemblages are not strongly related to structural characteristics of these water bodies.…”
Section: Discussionsupporting
confidence: 75%
“…Stream size was not related to either abundance or richness of squamates, as observed for frogs in the same study area (Tsuji-Nishikido and Menin 2011), indicating that lizard and snake assemblages are not strongly related to structural characteristics of these water bodies. Previous studies in central Amazonia have also shown that squamate assemblages are not affected by stream features, but mainly by the distance gradient in relation to streams (Fraga et al 2011;Faria et al 2019).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This discrepancy may simply reflect unequal sampling efforts. The methods we used for capture were diversified and effective for certain hosts groups, such as Teiidae and Tropiduridae, but are limited for many lizard species, mainly those that access subterranean microhabitats (Faria et al 2019). Indeed, Teiidae, Tropiduridae and a lizard species, U. superciliosus, were the hosts with highest parasite prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental filtering has been found in Amazonia for plants, frogs, lizards, snakes, and birds [15,[35][36][37][38][39][40][41][42][43]. For lizards, local assemblages may differ due to variation in individual abundance or species turnover along gradients of distance from water courses [31,44], elevation [45], climate seasonality [46], and number of trees [43,47]. Additionally, lizard assemblages may be indirectly structured by species turnover along gradients of canopy openness affecting the availability of thermoregulation sites [48,49], understory-plant density affecting the availability of foraging sites for perching species [50], and clay content in the soil affecting plant composition and food availability [43].…”
Section: Introductionmentioning
confidence: 99%